Temuan community of Kampung Orang Asli Batu 16, Gombak: Traditional knowledge of medicinal plants and evaluation of anti-inflammatory potential of selected plants / Siti Nor Azreen Abdul Manap - Siti Nor Azreen , Abdul Manap (2021)
The utilization of medicinal plants for the treatment of various ailments and health conditions is a common practice among the indigenous people or locally known as Orang Asli in Malaysia. However, traditional knowledge on medicinal plants used by Orang Asli has not been documented extensively. Therefore, the aim of this study was to document all the medicinal plants and their applications in treating ailments or health conditions by the Temuan tribe of Kampung Orang Asli Batu 16, Gombak, Selangor. This valuable traditional knowledge must be documented and preserved before it is lost due to modernization. Assessment of selected medicinal plants for their anti-inflammatory activity was conducted to provide evidence on the effectiveness of the medicinal plants in inflammation treatment. Data were collected from 11 respondents in the village using a semi-structured questionnaire with prior consent. Three medicinal plants such as Molineria latifolia, Tacca integrifolia, and Hymenocallis speciosa were selected for the evaluation of anti-inflammatory potential based on in vitro assay through inhibition of protein denaturation method. A total of 41 medicinal plant species belonging to 28 plant families were documented for their usage in the treatment of 37 ailments or health conditions. Plants of the family Zingiberaceae made up the largest number of medicinal plants (17.1%) followed by Fabaceae (9.8%) and Arecaceae (7.3%). Leaves (34.1%) are the most frequently used plant part for the preparation of herbal remedies. Although a variety of methods have been used for the preparation of herbal remedies, decoction (56.9%) is the most common method of preparation used by the Temuan tribe. In terms of mode of application, oral administration (68%) is the most common followed by being applied topically and bath with 14% and 10%, respectively. Bound topically (8%) is the least typical way of administration. Diabetes and fever are the most common ailments cured using medicinal plants. Parkia speciosa and Ficus deltoidea are the most commonly utilized plant species as remedies for various ailments in this study. The present findings on inhibition of protein denaturation of ethanolic and aqueous extracts of M. latifolia showed concentration-dependent inhibition within the range 65.63 ± 1.56% to 155.91 ± 2.15% of inhibition rate throughout the concentrations tested (100 – 500 μg/mL). Ethanolic extract of T. integrifolia leaves exhibited the highest (86.01 ± 4.04%) anti-inflammatory activity at a concentration of 100 μg/mL compared to their aqueous extract with only 31.88 ± 1.45% at a concentration of 300 μg/mL. Meanwhile, for extract of H. speciosa leaves, the aqueous extract had shown the highest suppression of protein denaturation with 87.18 ± 2.56% at a concentration of 200 μg/mL while only 42.68 ± 0.00% inhibition was observed for its ethanolic extract in the same concentration. All ethanolic extracts of these selected plants showed significant differences in inhibition activity compared to their aqueous extracts. The effect of indomethacin, a common anti-inflammatory drug, was found to be less when compared with these plant extract. Hence, the findings in this study verified the anti-inflammatory activity of the selected plants and support the claim by the Temuan that M. latifolia, T. integrifolia, and H. speciosa could alleviate their inflammation disorders.